Ausências, brechas e encontros: o professor tutor no estágio curricular supervisionado - Minato, Lauren Hundertmarck (2013)
This research was carried out at Programa de Pós-Graduação em Educação (PPGE) from Universidade Federal de Santa Maria (UFSM). The study is inserted into the Research Line “Formação docente, saberes e desenvolvimento profissional” (LP1), and sought to investigate the relations of tutor teachers with their own and their student teacher’s education through the Supervised Student Teaching (SST). The SST is one of the spaces of teacher practice in education teacher program and it offers pluralities in the relations established wherever it occurs – the school and the university – not only for the future teacher, but also, for the ones who are engaged in it. The research proposed studying the narratives by the investigated subjects: teachers of basic education schools of Santa Maria/RS, which receive students from teacher education programs, enrolled in SST courses, from UFSM, with the purpose to investigate how they characterize the orientation work inside SCT, space/time education in which they take part. Thus, tutor, in the text, presents the character of a teacher that works together with the future teacher. The research adopted a qualitative approach, characterized as a case study, with non-structured interviews, audio recorded, and carried out with each tutor individually, six in total, from the disciplines of Science, Biology, Portuguese Language and English Language. In this way, it was possible to identify different types of supervising and conceptions upon SST for each tutor teacher, as a help to the student teacher just when required, or seen as doubts and knowledge exchanges between both or, yet, as an interaction and collective construction among everybody who takes part into the SST, including also the orientating teacher, being possible, to identify in some tutors the responsibility for the student teacher education.